Chemical Composition, Antioxidant and In vitro Antibacterial Activities of Essential Oils of Mentha spicata Leaf from Tiaret Area (Algeria) - Selles, Sidi Mohammed Ammar; Kouidri, Mokhtaria; Bellik, Yuva; Amrane, Amar Ait; Belhamiti, Belkacem Tahar; Benia, Ahmed Redha; Hammoudi, Si Mohamed; Boukraa, Laid (Dhaka University Journal of Pharmaceutical Sciences, 2018)
The antioxidant and antibacterial activities and the composition of essential oil of Mentha spicata from Tiaret area were evaluated. The essential oil was obtained by hydrodistillation. The antioxidant activity was determined by DPPH radical scavenging assay and reducing power. The antimicrobial activity was evaluated by the broth microdilution method against seven strains isolated from diarrhea of young calves. The essential oil was analyzed by GCMS/ GC-FID. A total of 116 compounds amounting of 99.92% of the total component of the oil were identified. The major component of the oil was carvone (63.59%).The antioxidant activity by DPPH assay showed IC50 value of 21.1 ± 7.17 μg/ml, while the reducing power assay have resulted an EC50value of 2.28 ± 0.68 μg/ml. The results showed that the essential oil exhibited an MIC against all tested bacteria at 2.37 mg/ml to 4.75 mg/ml. The essential oil of M. spicata showed strong antioxidant and weak to moderate antibacterial activities. Dhaka Univ. J. Pharm. Sci. 17(1): 87-96, 2018 (June)